Effects of dietary polyphenol-rich plant products from grape or hop on pro-inflammatory gene expression in the intestine, nutrient digestibility and faecal microbiota of weaned pigs - Fiesel, Anja; Gessner, Denise K.; Most, Erika; Eder, Klaus; Justus Liebig University Giessen (My University, 2014)
BACKGROUND: Feeding polyphenol-rich plant products has been shown to increase the gain:feed ratio in growing pigs. The reason for this finding has not yet been elucidated. In order to find the reasons for an increase of the gain:feed ratio, this study investigated the effect of two polyphenol-rich dietary supplements, grape seed and grape marc meal extract (GSGME) or spent hops (SH), on gut morphology, apparent digestibility of nutrients, microbial composition in faeces and the expression of pro-inflammatory genes in the intestine of pigs. RESULTS: Pigs fed GSGME or SH showed an improved gain:feed ratio in comparison to the control group (P < 0.10 for GSGME, P < 0.05 for SH). Villus height:crypt depth ratio in duodenum and jejunum as well as apparent total tract digestibility of nutrients were unchanged in the groups receiving GSGME or SH in comparison to the control group. However, the groups receiving GSGME or SH revealed an increased faecal pH value, lower levels of volatile fatty acids and lower counts of Streptococcus spp. and Clostridium Cluster XIVa in the faecal microbiota (P < 0.05). Moreover, both treatment groups had a lower expression of various pro-inflammatory genes in duodenum, ileum and colon than the control group (P < 0.05). CONCLUSION: The present study suggests that dietary plant products rich in polyphenols are able to improve the gain:feed ratio in growing pigs. It is assumed that an alteration in the microbial composition and anti-inflammatory effects of the polyphenol-rich plant products in the intestine might contribute to this effect.
Keywords: polyphenol; pig; intestine; microbiota; ddc:630